Investigation of benzylisoquinoline alkaloid biosynthetic pathway and its transcriptional regulation in lotus. Issue 1 (1st June 2018) - Deng, Xianbao; Zhao, Li; Fang, Ting; Xiong, Yaqian; Ogutu, Collins; Yang, Dong; Vimolmangkang, Sornkanok; Liu, Yanling; Han, Yuepeng
Abstract: Lotus predominantly accumulates benzylisoquinoline alkaloids (BIAs), but their biosynthesis and regulation remain unclear. Here, we investigated structural and regulatory genes involved in BIA accumulation in lotus. Two clustered CYP80 genes were identified to be responsible for the biosynthesis of bis-BIAs and aporphine-type BIAs, respectively, and their tissue-specific expression causes divergence in alkaloid component between leaf and embryo. In contrast with the common ( S )-reticuline precursor for most BIAs, aporphine alkaloids in lotus leaf may result from the ( S )- N -methylcoclaurine precursor. Structural diversity of BIA alkaloids in the leaf is attributed to enzymatic modifications, including intramolecular C–C phenol coupling on ring A and methylation and demethylation at certain positions. Additionally, most BIA biosynthetic pathway genes show higher levels of expression in the leaf of high-BIA cultivar compared with low-BIA cultivar, suggesting transcriptional regulation of BIA accumulation in lotus. Five transcription factors, including three MYBs, one ethylene-responsive factor, and one basic helix–loop–helix (bHLH), were identified to be candidate regulators of BIA biosynthesis in lotus. Our study reveals a BIA biosynthetic pathway and its transcriptional regulation in lotus, which will enable a deeper understanding of BIA biosynthesis in plants. Synthesis of medicinal compounds in lotus: Researchers at the Chinese Academy of Sciences have discovered the genes in lotus responsible for the synthesis of benzylisoquinole alkaloids (BIAs), a diverse set of pharmacologically significant plant metabolites. By comparing gene expression in two lotus varieties, a high- and low-BIA cultivar, they identified the genes that were active during BIA biosynthesis as well as five transcription factors which regulate the process. One of the biosynthesis genes is expressed more strongly in the embryo and another in the leaves, leading to the accumulation of different types of BIAs in these tissues. Although many of these genes are related to known BIA synthesis genes in other species, identifying the lotus equivalents not only reveals the particulars of the process in this species but also expands our understanding of BIA synthesis in general.